Morphological Parameters of 29994 sperm in a fertile male population—based on Papanicolaou staining and SSA-II Plus - Fu, Longlong; Zhou, Fang; Chen, Guoping; Yuan, Renpei; Li, Wenjie; Qiu, Shi; Tang, Liang; Liu, Wenshu; Gu, Yiqun; Lu, Wenhong (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to provide reference data for sperm morphology in a healthy, fertile male population providing a foundation for future studies on male infertility assessment and sperm selection in assisted reproductive technologies.MethodsThe study included 21 healthy male participants, all of whom had partners who conceived within the past 12 months. Sperm samples were collected according to WHO guidelines and stained using the Papanicolaou method. Sperm morphology parameters, including head length, width, area, perimeter, ellipticity, and acrosome area, were measured using the Suiplus SSA-II Computer-Assisted Sperm Analysis (CASA) system. Statistical comparisons were made between CASA and traditional manual methods.ResultsThe percentage of sperm with normal head morphology was 9.98%. Detailed sperm head measurements, including length, width, and area, were provided as reference values for the healthy male population. The CASA system demonstrated the ability to reduce subjective errors and showed no significant differences in sperm count and motility compared to traditional methods.ConclusionThis study provides precise sperm morphology reference values that enhance male infertility diagnostics and treatment, particularly in sperm selection for assisted reproductive technologies like ICSI.